Social equity is key to sustainable ocean governance - Crosman, Katherine; Allison, Edward H.; Ota, Yoshitaka; Cisneros-Montemayor, Andrés; Singh, Gerald; Swartz, Wilf; Bailey, Megan; Barclay, Kate; Blume, Grant; Colléter, Mathieu; Fabinyi, Michael; Faustman, Elaine; et al. (Springer, 2022)
Calls to address social equity in ocean governance are expanding. Yet ‘equity’ is seldom clearly defined. Here we present a framework to support contextually-informed assessment of equity in ocean governance. Guiding questions include: (1) Where and (2) Why is equity being examined? (3) Equity for or amongst Whom? (4) What is being distributed? (5) When is equity considered? And (6) How do governance structures impact equity? The framework supports consistent operationalization of equity, challenges oversimplification, and allows evaluation of progress. It is a step toward securing the equitable ocean governance already reflected in national and international commitments.